2021
DOI: 10.1002/advs.202102510
|View full text |Cite
|
Sign up to set email alerts
|

Amphibious Transport of Fluids and Solids by Soft Magnetic Carpets

Abstract: One of the major challenges in modern robotics is controlling micromanipulation by active and adaptive materials. In the respiratory system, such actuation enables pathogen clearance by means of motile cilia. While various types of artificial cilia have been engineered recently, they often involve complex manufacturing protocols and focus on transporting liquids only. Here, soft magnetic carpets are created via an easy self‐assembly route based on the Rosensweig instability. These carpets can transport not onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 54 publications
0
57
0
Order By: Relevance
“…Some researchers were able to circumvent this issue by embedding small ferrous particles within a soft‐bodied matrix as composites. [ 490,566,567 ] Exciting recent work examined the use of magnetorheological fluids in soft robots for magnetic control and operation, [ 568,569 ] while other researchers demonstrated the transportation of fluids and solids across a “soft magnetic carpet.” [ 570 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers were able to circumvent this issue by embedding small ferrous particles within a soft‐bodied matrix as composites. [ 490,566,567 ] Exciting recent work examined the use of magnetorheological fluids in soft robots for magnetic control and operation, [ 568,569 ] while other researchers demonstrated the transportation of fluids and solids across a “soft magnetic carpet.” [ 570 ]…”
Section: Resultsmentioning
confidence: 99%
“…[490,566,567] Exciting recent work examined the use of magnetorheological fluids in soft robots for magnetic control and operation, [568,569] while other researchers demonstrated the transportation of fluids and solids across a "soft magnetic carpet." [570] Optical media were only seen in 23 actuators and five sensors, a small quantity relative to the 342 soft robotic components recorded. A typical example of optical media includes ultraviolet radiation.…”
Section: Function Mediamentioning
confidence: 99%
“…The light-controllable cilia were fabricated using Diarylethene and are capable of transporting objects, demonstrated to transport the polystyrene bead (PB) of 1 mm in diameter. Recent bioinspired artificial cilia established from natural cilia for transporting ability are reported elsewhere [ 23 , 30 , 31 , 34 , 36 , 37 , 38 , 39 , 40 ]. Inspired by the starfish surface, researchers designed ciliary bands [ 29 ], which can be actuated by ultrasound.…”
Section: From Natural Cilia To Artificial Ciliamentioning
confidence: 99%
“…On the other hand, a single row or column of artificial cilia responded to the dual magnets comprised junction induced magnetic field, which can create precise unidirectional wave motion. Double the magnet junctions have been introduced as a spectacular milestone in droplet manipulation [ 37 , 39 ]. Song et al [ 39 ] demonstrated that the artificial cilia that moved the water droplet using dual magnets comprised junctions induced unidirectional wave motion using a single column of the ciliary array.…”
Section: Artificial Cilia For Microfluidic Applicationsmentioning
confidence: 99%
“…We explore this strategy by creating “soft magnetic carpets” (SMCs) through a scalable self-assembly procedure that is based on the Rosensweig instability. Recently, we used similar SMCs with no infusion layer to transport solid and liquid cargos ( 32 ). In the current work, while the carpets are infused with a liquid, they also contain soft magnetic pillars that align with magnetic fields.…”
mentioning
confidence: 99%